The Roles and Challenges of Corporate Social Responsibility and the Initiatives taken by Indian Public and Private Industries - Acharya, Mohit (Journal of Advanced Research in Public Policy and Administration, 2022)
The idea of corporate social responsibility, also known as CSR, has been around for quite some time in the Indian industrial sector. CSR can be understood as the responsibility of businesses and industrial organizations to be accountable to the society as a whole as well as to the stakeholders they serve. Many organizations, both in the public and private sectors, have a variety of perspectives regarding it, such as “corporate philanthropy, corporate environment responsibility, corporate accountability, corporate science, corporate citizenship, social performance, sustainable responsible business form of corporate, strategic philanthropy, sustainability, corporate moral agency, social entrepreneurship, or Corporate Social Responsibility (CSR)” as a business process. The Corporate Social Responsibility (CSR) of today is an essential component of any successful business strategy, with the primary emphasis being placed on long-term sustainability and engagement with both internal and external stakeholders. CSR leading to a strategy that is centered on people. Business executives and organizations should place a higher focus on health care and education since these areas directly benefit the general public. The notion of CSR is always being refined within the Indian manufacturing sector. It is treated as an essential component of the operations of the business and is given the same Key Performance Areas (KPAs) and metrics as the others. When it comes to the planning and monitoring of CSR initiatives, several companies have employed a variety of project management approaches. There is a pressing need for the Indian business industry to place a greater focus on Corporate Social Responsibility (CSR) operations, since this will go a long way toward maintaining organizations’ development and excellence over the long term. In addition, the formulation of novel approaches for the purpose of meeting the growing issues that are being brought up by the accelerating changes that are altering in the long term. Therefore, “Corporate Social Responsibility (CSR) is the commitment or engagement of a business to contribute to sustainable economic development.